Al-Wathaniah fī Syi'ir ilā Ummī lī Mahmūd Darwīsy (al Dirāsāt al Sīmiyāiyyah 'inda Roland Bārthes) - Ashfiyah, Za’imatil; Ulyah, Rika Fithratul; Zaini, Muhammad Ardy (Journal of Language Intelligence and Culture, 2022)
This research discusses the patriotism found in Mahmoud Darwish's poetry, entitled "To My Mother", by studying semiotics at Roland Barthes. This is done to find out the declarative and suggestive significance related to the sense of patriotism in Mahmoud Darwish's poetry to my mother and the effect of poetry on the reader. The researcher used the qualitative descriptive approach with the theory of analysis to study the semiotics of Roland Barthes, which explains the meaning of patriotism through declarative significance, suggestive significance, and superstitious significance. It clarifies the linguistic declarative signification according to the actual meaning, while the suggestive gives the meaning of the poetry in depth. The metaphorical signification is an ideological process of suggestive that serves to provide justification and disclosure of the dominant values ??that apply during a certain time period. The primary data in this scientific research is Poetry To My Mother by Mahmoud Darwish and the secondary sources support books related to scientific research. From the analysis, it is known that the declarative significance is that this poetry indicates the poet's longing for his mother, and the suggestive significance of this poem is the poet's longing for his homeland. Likewise, the influence of Mahmoud Darwish's poetry on the readers made them feel nostalgic in the words about longing for the motherland far from their lives.